2021
DOI: 10.46729/ijstm.v2i3.222
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Of Internationalization Of Small And Medium Micro Enterprises In SAWO Leather Crafts, Magetan District, East Java, Indonesia

Abstract: The Magetan leather handicraft business is one of the long-established and surviving SMEs and contributes to the creation of employment and income for the community. Currently, the marketing of leather handicraft products is still limited to meeting local and national needs so that limited market demand makes leather handicraft difficult to develop. Globalization and increasingly advanced information technology have become opportunities for the Magetanleathercraft industry to penetrate the international market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
1
1
0
1
Order By: Relevance
“…Study Sultoni et al [44] found that it was necessary to increase brand awareness and quality of SME products in Madura to make them more attractive in the international market. The limitations of SMEs in the internationalization process are also found in research by Purwanto [45]; the study results indicate that there are obstacles to the internationalization of the Magetan leathercraft business, namely complicated international trade procedures for SMEs, no overseas marketing channels, and limited resources.…”
Section: Empirical Reviewsupporting
confidence: 56%
“…Study Sultoni et al [44] found that it was necessary to increase brand awareness and quality of SME products in Madura to make them more attractive in the international market. The limitations of SMEs in the internationalization process are also found in research by Purwanto [45]; the study results indicate that there are obstacles to the internationalization of the Magetan leathercraft business, namely complicated international trade procedures for SMEs, no overseas marketing channels, and limited resources.…”
Section: Empirical Reviewsupporting
confidence: 56%
“…Recently, Sultoni et al [45] discovered that improving brand awareness and product quality is essential for Madura SMEs to be more appealing in the global market. Similarly, the research shows that limited resources, complicated international trade procedures, and a lack of overseas marketing channels challenge the internationalization of Magetan's leather craft business [46]. Furthermore, that several problems in the context of heading to an international market in the culinary cluster UKM represented by the Bakso Klenger UKM, Jember Regency, had been identified based on fish bone analysis techniques.…”
Section: Empirical Reviewmentioning
confidence: 96%
“…Pengembangan dunia e-commerce saat ini meningkat dengan adanya beberapa fitur yang mempermudah yang disuguhkan untuk membuat banyak orang menjadi tertarik. Pengelolaan penjualan produk di desa baik makanan ataupun kerajinan di fitur pemasaran dengan tujuan mempertemukan penjual dan pembeli tanpa harus bertemu secara langsung bertatap muka (Gupta et al, 2021;Purwanto, 2021). Hadirnya pengelolaan ini tersebut mempersingkat waktu saling berhubungan, antara perusahaan dengan entitas bisnis lainnya.…”
Section: Melengkapi Produk Desa Fitur Pemasaranunclassified